Integrated Mechanical and Eco-Economical Assessments of Fly Ash-Based Geopolymer Concrete - Qasim Shaukat Khan; Raja Hilal Ahmad; Asad Ullah Qazi; Syed Minhaj Saleem Kazmi; Muhammad Junaid Munir; Muhammad Hassan Javed (Buildings, 2025)
This research evaluates the mechanical properties, environmental impacts, and cost-effectiveness of Hub Coal fly ash (FA)-based geopolymer concrete (FAGPC) as a sustainable alternative to ordinary Portland cement (OPC) concrete. This local FA has not been investigated previously. A total of 24 FAGPC mixes were tested under both ambient and heat curing conditions, varying the molarities of sodium hydroxide (NaOH) solution (10-M, 12-M 14-M and 16-M), sodium silicate to sodium hydroxide (Na2SiO3/NaOH) ratios (1.5, 2.0, and 2.5), and alkaline activator solution to fly ash (AAS/FA) ratios (0.5 and 0.6). The test results demonstrated that increasing NaOH molarity enhances the compressive strength (CS.) by 145% under ambient curing, with a peak CS. of 32.8 MPa at 16-M NaOH, and similarly, flexural strength (FS.) increases by 90% with a maximum FS. of 6.5 MPa at 14-M NaOH. Conversely, increasing the Na2SiO3/NaOH ratio to 2.5 reduced the CS. and FS. of ambient-cured specimens by 12.5% and 10.5%, respectively. Microstructural analysis revealed that higher NaOH molarity produced a denser, more homogeneous matrix, supported by increased Si–O–Al bond formation observed through energy-dispersive X-ray spectrometry. Environmentally, FAGPC demonstrated a 35–40% reduction in embodied CO2 emissions compared to OPC, although the production costs of FAGPC were 30–35% higher, largely due to the expense of alkaline activators. These findings highlight the potential of FAGPC as a low-carbon alternative to OPC concrete, balancing enhanced mechanical performance with sustainability. New, green, and cheap activation solutions are sought for a new generation of more sustainable and affordable FAGPC.